The influence of career, experience, and professionalism on audit quality at the audit board of the Republic of Indonesia representative of South Sumatera Province - Fazmi, Andrian; Widiyanti, Marlina; Yusuf, Muhammad; Perizade, Badia (International research journal of management, IT and social sciences, 2022)
This study aims to determine and analyze the influence of career, experience, and professionalism on audit quality at The Audit Board of The Republic of Indonesia Representative of South Sumatera Province. The sampling technique in this study was by using the sampling method, namely as many as 108 employees consisting of Intermediate Expert Auditor, Junior Expert Auditor, and First Expert Auditor. Data analysis in this study used multiple linear regression analysis. The study results show that career, experience, and professionalism variables partially have a positive and significant effect on audit quality at The Audit Board of The Republic of Indonesia Representative of South Sumatera Province. The experience variable significantly influences audit quality more than the career and professionalism variables. In addition, career, experience, and professionalism simultaneously positively and significantly affect audit quality at The Audit Board of The Republic of Indonesia Representative of South Sumatera Province.